The Influence of Cost Incurred on the Critical Success Factors of SMRs in the UAE - AL TENEIJI, SAIF MOHAMMED (2018)
The study began with the objective to understand the influence that the cost incurred has on the critical success factors of the SMRs. SMRs are a promising technology in the nuclear sector which can provide clean energy while being safer than the large reactors. Thus, to realize the study’s objectives, the primary independent variable (Cost Incurred) and the primary dependent variable (Success Factors) were categorized into four sub-variables each. Cost incurred was measured via the four sub-variables: Higher Profit Margins, Low Cost Encourages Investment, Low Cost Encourages Economic Cost and Easy Impacts Projection on Costs. The critical success factors were categorized into the following sub-variables: Governments Regulatory Framework, Government Supporting in Grid Development, Geopolitical Collaborations and Large Space Availability. A questionnaire was developed and distributed to the employees of UAE’s nuclear power plant. The results obtained were analysed through SPSS. It was found that there was a statistically significant correlation between Cost Incurred and Success factors. Subsequently, multiple regression was carried out and the regression was significant thereby a predictive model of the relationship between the cost incurred and the success factors was developed.